Au-Pt nanoparticles in amine functionalized MCM-41: catalytic evaluation in hydrogenation reactions - Joseph, Trissa; Kumar, K. Vijay; Ramaswamy, A. V.; Halligudi, Shivaraj B. (Catalysis Communications, 2007)
Nano-sized Au-Pt nanoparticles (Au-Pt-bi-MNPs) have been synthesized by the simultaneous reduction of HAuCl4 and HPtCl6 by NaBH4 inside the channels of amine functionalized Si-MCM-41 (NH2-Si-MCM-41) at ambient conditions. These materials were characterized using chemical analysis, UV-vis, XPS, XRD, FT-IR, Surface area and TEM analysis. The size of these alloyed nanoparticles (bi-MNPs) were found in the range of 2-4 nm. These nanoparticles were evaluated to study their catalytic activities towards hydrogenation of aromatic nitro compounds. The catalytic activity of the Au-Pt bi-MNPs was found to be superior to monometallic An nanoparticles. (c) 2006 Published by Elsevier B.V.
Keywords: amine-functionalized MCM-41; Au-Pt nanoparticles; Catalytic hydrogenation